Proeses que les barceloneses dones han ostentat en este siti de l'any 1706: una aproximació filològica. - SOGUES MARCO, MARC (Scripta, 2017)
During the Bourbon siege of 1706, the inhabitants of Barcelona launched a counter-offensive in order to recover the fortress of Montjuïc. The women of the city played a significant role in this actions and their participation was praised in an account of events written in verse that circulated through a libel entitled Proeses que les barceloneses dones han ostentat en este siti de l’any 1706 (Feats that Barcelona women have shown in this site of the year 1706). This work is well known in the field of historiography, but nonetheless, until this moment, no approach has been proposed providing the reader with a philologically reliable, updated and commented edition of the complete poem. Therefore this is the objective of the present work. To achieve this objective, the article is structured in three parts: 1) the framing of the text in its historical and cultural context; 2) its description and interpretation in the light of the methodological and conceptual tools of literary theory and comparative literature; and 3) the establishment of the text based on the critical comparison of all the available printed testimonials and its edition, with the spelling adaptation and the corresponding critical apparatus..